Modelling of Functional Gradient Porous Structure and its Fabrication using Additive Manufacturing Process. (2018) - Suresh Babu, A.; Binish, K.M.; Jaivignesh, M.; Sugavaneswaran, M.
Abstract: A porous structure contains pores or voids and its load withstanding capacity varies greatly with the distribution of porosity. Gradient porous structures have many advantages over uniform porous structures. However, it is difficult to manufacture and determine mechanical properties of such structures, as the setup time and the cost of fabricating them in batches are very high. In this work, the effect of porosity gradient on the compressive strength of the structures with three different porosity distribution namely uniform porosity, porosity gradient from 30% to 70% and gradient from 20% to 80% are studied. The initial stage involves the development of mathematical model of normal and gradient porous structure based on governing equation of gyroid, which is a triply periodic minimal surface. CAD models of normal porous and gradient porous structures are generated. Developed structures are manufactured by Polyjet additive manufacturing method with Vero Clear as the build material and are experimentally tested under compressive loading conditions. The CAD models are numerically analysed for the same conditions using data from the experiments. The variations in maximum stress values between experimental and numerical results are small and thus it can be concluded that the strength of any mathematically developed CAD model of a gradient porous structure can be determined and analysed with fair accuracy using Finite Element Analysis (FEA) method giving comparable results with experimental values and is a cost saving approach. In addition to this, it can be concluded that such complex structures can be fabricated using additive manufacturing technique